The 50 Most Cited Articles in the Indications, Risk Factors, Techniques, and Outcomes of ACL Revision Surgery - Ennis, Hayley E.; Bondar, Kevin; McCormick, Johnathon; Chen, Clark Jia-Long; Donnally, Chester J., III; Kaplan, Lee (The Journal of Knee Surgery, 2020)
The rate of anterior cruciate ligament (ACL) retear remains high and revision ACL reconstruction has worse outcomes compared with primaries. To make advances in this area, a strong understanding of influential research is necessary. One method for systematically evaluating the literature is by citation analysis. This article aims to establish and evaluate “classic” articles. With consideration of these articles, this article also aims to evaluate gaps in the field and determine where future research should be directed. The general approach for data collection and analysis consisted of planning objectives, employing a defined strategy, reviewing search results using a multistep and multiauthor approach with specific screening criteria, and analyzing data. The collective number of citations for all publications within the list was 5,203 with an average of 104 citations per publication. “Biomechanical Measures during Landing and Postural Stability Predict Second Anterior Cruciate Ligament Injury after Anterior Cruciate Ligament Reconstruction and Return to Sport” by Paterno et al contained both the highest number of total citations and the highest number of citations per year, with 403 total citations and 43.9 citations per year. The most recurring level of evidence were level II (n = 18) and level III (n = 17). “Clinical Outcomes” was the most common article type (n = 20) followed by “Risk Factors” (n = 10). TheAmerican Journal of Sports Medicine had the highest recorded Cite Factor with over 50% of the articles (n = 27) published. The most productive authors included R.W. Wright (n = 6), S.D. Barber-Westin (n = 5), F.R. Noyes (n = 5), and K.P. Spindler (n = 5). Historically, influential studies have been published in the realms of clinical outcome and risk factor identification. It has been established that revision ACL reconstruction has worse outcomes and more high-level studies are needed. Additionally, prospective studies that apply the knowledge for current known risk factor mitigation are needed to determine if graft tear rates can be lowered.
Keywords: ACL revision; bibliometric; citation review